Errata in ``Lectures on the dynamical Yang-Baxter equations''
by P. Etingof & O. Schiffmann, math.QA/9908064 v2, version 18 May 2000.
Errata collected by Tom H. Koornwinder .
Last modified: 23 May 2000.
p.6, l.7 of Example 1: Interchange in the tensor product v_- and v_+
p.25, l.12 Replacse by:
$$=\sum_i \Phi_{\lambda-wt(v)}^w \Phi_\lambda^v x_i^2 x_\lambda
+ (\sum_i (x_i^2)_3 - 2\lambda_3) \Phi_{\lambda-wt(v)}^w \Phi_\lambda^v
x_\lambda.$$
p.25, l.12 from below: On the rhs replace -2 by +2.
p.27, l.3 of section 9.2: Replace in $v_{\mu-\nu}^*$ and $v_\mu$ the
character v by the character x.
p.27, l.5 of section 9.2: Replace $V[\nu]$ by $V$
p.38 [GN]: replace absense by absence